The live-streaming strategy for competitive manufacturers considering information disclosure and product heterogeneity - Liwen Liu; Qing Wang; Zonghuo Li; Tingting Wu; Yuan Yuan (PLoS ONE, 2026)
Live-streaming has become increasingly populous in recent years and a large body of manufacturers such as Apple and Huawei have adopted live-streaming strategies. Despite the live-streaming can disclose product information and enhance consumer utilities, consumers may leave the market if they realize that the product is not fit for them after watching the live-streaming. This paper studies the opening strategy of live-streaming for competitive manufacturers who sell products with differential quality. Four cases regarding whether the manufacturers open a live-streaming channel to disclose product information are modeled, namely, NN (no manufacturer opens), DN/ND (one manufacturer opens), and DD (both manufacturers open). We further analyze how product quality influences live-streaming strategies. The result shows that adopting live-streaming allows a manufacturer to charge higher prices, whereas competitor live-streaming adoption exerts downward price pressure. Interestingly, live-streaming does not universally benefit manufacturers. Rather, for the high-quality manufacturer, the manufacturer benefits from the live-streaming channel when the fitness of its product is mid-value. However, for the low-quality manufacturer, the manufacturer will be better off by opening a live-streaming channel when the fitness of its product is large.